Correlation between gestational age of the foetus and ultrasonographic placental thickness - Mungamuru, Sowmya; Munivenkatappa, Swetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Study aimed to find the correlation between gestational age of the foetus and ultrasonographic placental thickness. Methods: This hospital based cross-sectional study conducted at department of Narayana medical college and hospital, Chinthareddypalem, Nellore. The study includes, 100 pregnant women admitted in hospital at more than 28 weeks to 40 weeks. Ultrasonographic measurement of placental thickness taken and correlated with other parameters like BPD, FC, AC, HC. Results: The mean age of participants was 25.95±2.59yrs of age, with minimum age of 21yrs and maximum age of 32 yrs pregnant women. The Strength of association of GA with PT was r=0.087, p<0.01; GA estimated by FL with PT was r=0.884, p<0.01; GA estimated by BPD with PT was r=0.902, p<0.01; and GA estimated by AC with PT was r=0.898, p<0.01. Conclusions: The study concluded that there is a strong positive strength of association between the gestational age and placental thickness.